Pharmacokinetics of Carboplatin in a One‐Year‐Old Anuric Boy Undergoing Hemodialysis and a Review of the Literature. Issue 5 (27th April 2015) - Kamei, Koichi; Sako, Mayumi; Ishikawa, Tomoaki; Sato, Mai; Ogura, Masao; Uno, Teruaki; Kiyotani, Chikako; Mori, Tetsuya; Tanaka, Hideaki; Ito, Shuichi; Nakamura, Hidefumi
Abstract There have been few reports of carboplatin‐based chemotherapy for anuric infants. As we had a chance to treat a one‐year‐old anuric hepatoblastoma patient with carboplatin, we performed a pharmacokinetic analysis and examined the optimal treatment strategy. A one‐year‐old anuric boy under peritoneal dialysis was diagnosed with hepatoblastoma. Surgical resection was performed, and administration of carboplatin was scheduled postoperatively aiming at 5 mg·min/mL of the area under the curve from the time of dosing to the time of the last observation (AUC0‐t). We set the initial dose at 50 mg, higher than that calculated by the Calvert formula (34 mg); the time from the end of carboplatin infusion to the initiation of hemodialysis at 2 h; and the hemodialysis duration at 24 h. The actual AUC0‐t was 3.05 mg·min/mL because the elimination half‐lives before and during hemodialysis were shorter than expected. The AUC0‐t after the second dose (100 mg) and the third dose (80 mg) were 7.00 and 4.68 mg·min/mL, respectively. The Calvert formula is not suitable for hemodialysis patients because removal of platinum by hemodialysis is not taken into account. It appears that extrarenal clearance in anuric infants is different from that in adults. We obtained an optimal AUC0‐t using a dose of 80 mg (200 mg/m2), setting the time from the end of carboplatin infusion to the initiation of hemodialysis at 2 h, and performing 8‐h hemodialysis. Further accumulation of the pharmacokinetic data of carboplatin is necessary for anuric children.